The First International Mini-Symposium on Methionine Restriction and Lifespan - Ables, Gene P.; Brown-Borg, Holly M.; Buffenstein, Rochelle; Church, Christopher D.; Elshorbagy, Amany K.; Gladyshev, Vadim N.; Huang, Tsang-hai; Miller, Richard A.; Mitchell, James R.; Richie, John P.; Rogina, Blanka; Stipanuk, Martha H.; et al. (Frontiers in Genetics, 2014)
It has been 20 years since the Orentreich Foundation for the Advancement of Science, under the leadership Dr. Norman Orentreich, first reported that low methionine (Met) ingestion by rats extends lifespan [1]. Since then, several studies have replicated the effects of dietary methionine restriction (MR) in delaying age-related diseases [2–5]. We report the abstracts from the First International Mini-Symposium on Methionine Restriction and Lifespan held in Tarrytown, NY last September 2013. The goals were 1) to gather researchers with an interest in methionine restriction and lifespan, 2) to exchange knowledge, 3) to generate ideas for future investigations, and 4) to strengthen relationships within this community. The presentations highlighted the importance of research on cysteine, growth hormone (GH), and ATF4 in the paradigm of aging. In addition, the effects of dietary restriction or MR in the kidneys, liver, bones and the adipose tissue were discussed. The symposium also emphasized the value of other species, e.g. the naked mole rat, Brandt’s bat and drosophila in aging research. Overall, the symposium consolidated scientists with similar research interests and provided opportunities to conduct future collaborative studies.